PERTUMBUHAN TIGA JENIS KIMPUL (Xanthosoma spp.) P PADA KETINGGIAN TEMPAT BERBEDA - Endang Anggarwulan; Widya Mudyantini; Yuniar Nilawati (Agric, 2015)
Indonesian society has a consumption pattern dominated staple grains group. To reduce dependence on other countries for imports of foodstuffs, need to diversification their meal using existing biodiversity. One of the crops that can be developed is the cocoyam (Xanthosoma spp.) potential as a source of carbohydrate. Cocoyam can be grown in the lowland to the mountains with a height of up to 1300 meters above sea level. Therefore it is necessary to find the most appropriate planting site so that plants can grow and develop optimally. This study aimed to determine the growth of three types of new cocoyam at a different altitude variation. This study was conducted in two different regions of altitude, is Tawangmangu (1200 m above sea level) and Klaten (98 m above sea level). Observations using three different types of cocoyam, the tuber white, purple and yellow. Each type grown in both altitude with 10 replications each. The observations were obtained include fresh weight, dry weight, number of leaves, chlorophyll and carotenoid levels were analyzed by unpaired t test and ANOVA test at 95% confidence level. The results of this study indicate that tuber white, purple and yellow tuber are planted in the lowlands (Klaten) and highlands (Tawangmangu) had significant results in the measurement of plant height, fresh weight, dry weight, and chlorophyll and carotenoid levels have significantly different results, but not the parameters of the number of leaves. Height and weight of the fresh plantin Klaten higher than in Tawangmangu, while the white tuber dry weight in Tawangmangu higher than other treatments. The levels of chlorophyll and carotenoid yellow tuber is the highest in Klaten than others.